2015
DOI: 10.1002/app.42864
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the polymorphism of cellulose on the formation of nanocrystals and their application in chitosan/nanocellulose composites

Abstract: In this study, we evaluated the physicochemical properties of the chitosan/nanocellulose composites. Wide-angle X-ray scattering was applied to define the supermolecular structure of the materials, the laser diffracting technique was used to characterize the particle sizes, and scanning electron microscopy was used to evaluate the morphologies of the samples. The tensile properties of the composite films were also determined. Cellulose pulp was mercerized with 16% sodium hydroxide to give only cellulose II. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 50 publications
6
38
0
Order By: Relevance
“…Not only Atef et al but other research groups [61,62] too showed that due to good dispersion, low content of nanofiller (CNC) in polymer matrix (polylactide) is the best in terms of enhancement of mechanical properties. This hypothesis is also supported by this and our previous work [28,40], but stays in opposite to Khan et al [63] who claimed that 5% of CNC is optimal for chitosan. It comes as no surprise that aspect ratio of a filler, its interaction with polymer matrix, and uniform dispersion of filler are the main factors limiting mechanical properties of composites [63].…”
Section: Mechanical and Morphological Properties Of Compositessupporting
confidence: 86%
See 3 more Smart Citations
“…Not only Atef et al but other research groups [61,62] too showed that due to good dispersion, low content of nanofiller (CNC) in polymer matrix (polylactide) is the best in terms of enhancement of mechanical properties. This hypothesis is also supported by this and our previous work [28,40], but stays in opposite to Khan et al [63] who claimed that 5% of CNC is optimal for chitosan. It comes as no surprise that aspect ratio of a filler, its interaction with polymer matrix, and uniform dispersion of filler are the main factors limiting mechanical properties of composites [63].…”
Section: Mechanical and Morphological Properties Of Compositessupporting
confidence: 86%
“…Accordingly, it can be concluded that sample of CNC I consisted of slightly larger amount of particles up to 220 nm, but it was also characterized with large volume of micrometric fraction. In the study on acidic hydrolysis of cellulose I and cellulose II [28], it was found that even though fraction of CNC II nanometric particles was higher than of CNC I, the micrometric particles of CNC I were significantly bigger than those of CNC II (max. 3580 and 1990 nm for CNC I and CNC II, respectively).…”
Section: Supermolecular and Chemical Structure Of Fillersmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, even chitosan films filled with unmodified nanometric cellulose exhibit high mechanical properties. Chitosan composites filled with 5% of nanocrystalline C I were found to be characterized with better tensile properties than analogous composites with nanocrystalline C II . It is worth emphasizing that in each case values of Young's modulus (YM) and tensile strength (TS) were higher than for pristine chitosan.…”
Section: Introductionmentioning
confidence: 96%